Nuevas citas para la avifauna argentina - Narosky, Samuel (1983)
Argentine birds new sightings. Presence of Pitangus lictor outside its range: a Lesser Kiskadee, the distribution of witch reaches northern Bolivia and Central Brazil, according to existing data, was seen al Los Talas, Buenos Aires Providence, on May 6, 1979. Three weeks later, it was captured by Juan Klimaitis. It presence in Argentine is new and it is strange that, although an insectivorous birds, it was found in winter. Observation of a Commun Dowitcher of the genus Limnodromus: there are differing opinion about the presence of Limnodromus acolopaseus in Argentine. The only specimen taken so far in this country is a female of L. scolopaseus. Since it is most difficult to separate the two species much of the literature about the distribution in South America may be wrong. A Common Dowitcher was seen and photographed near Cape San Antonio, Buenos Aires Province, on December 6, 1977. Amongst other specialists consulted was Dr. Franf A. Pitelka; he believe that it was a male of L. scolopaseus in its first autumn plumage. This would represent the second record of this species in the country. Discovery of Aphryza virgata in Argentine territory: lt is not difficult to imagine that the Sud Bird which migrates from North America to the far south of Chile could also reach the Argntine sector of Tierra del Fuego. This distribution was confirmed by the observation of an individual on the beaches near Ushuaia on February 19, 1978. This is the first record for Argentine.